The role of teachers’ intelligence conceptions, teaching beliefs and self-efficacy on classroom management practices - Catalano, Maria Gaetana; Vecchio, Giovanni Maria; Perucchini, Paola (Ricerche di Psicologia - Open Access, 2022)
Substantial evidence has been collected over decades of research on the relationships between optimal classroom management and student learning. In addition, there is a growing body of research on teachers’ beliefs, in which their relationships with teachers’ practices is viewed as significant. This study investigated classroom management practices in a sample of 1,056 Italian teachers working from pre-primary to secondary school, to analyse the differences by school level and teaching experience, and their associations with three categories of teachers’ beliefs: self-efficacy, teaching beliefs and intelligence conceptions. Three dimensions of classroom management were considered: educational relationships, active strategies and emotion regulation. The results show that teachers differ in their practices in relation to school level and years of experience, with associations between different categories of beliefs highlighted. Classroom management was positively linked to self-efficacy, constructive teaching beliefs and constructive intelligence conceptions, and negatively linked to traditional teaching beliefs and innate intelligence conceptions. Hierarchical multiple regression analyses that considered the three dimensions of classroom management as dependent variables highlighted the concurrent contribution of: innate and constructive teaching beliefs for educational relationships; school level, intelligence conceptions, constructive teaching beliefs and self-efficacy on classroom management for active strategies; and school level for emotion regulation. These results confirm the strong relationships between classroom management and teachers’ beliefs and conceptions. Thus, it is important for teachers to develop reflective processes of their own practices.